2019
DOI: 10.1111/ijn.12723
|View full text |Cite
|
Sign up to set email alerts
|

De‐implementation of tradition‐based practices in critical care: A qualitative study

Abstract: Aim To explore the process of tradition‐based practice (TBP) de‐implementation by critical care nurses. Background Ritualistic and routine practices have been described as sacred cows or TBPs. Many clinical practices have insufficient or no evidence and may lead to poor patient outcomes. De‐implementation (termination) of potentially harmful, ineffective, or non cost‐effective TBP is necessary to facilitate evidence‐based practice (EBP) in the clinical setting. Design Descriptive qualitative inquiry guided thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
10
0
5
Order By: Relevance
“…The next step is to translate these 'Choosing Wisely' lists into action [13]. To actually reduce the use of low-value nursing procedures, awareness should be created for the 'Choosing Wisely' lists and effective de-implementation strategies need to be developed and executed [7,14,15]. These deimplementation strategies should be theory-and evidencebased and informed by analysis of barriers and facilitators that influence the use of low-value care, since this is expected to increase the adherence, adoption, and effectiveness of these de-implementation strategies [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The next step is to translate these 'Choosing Wisely' lists into action [13]. To actually reduce the use of low-value nursing procedures, awareness should be created for the 'Choosing Wisely' lists and effective de-implementation strategies need to be developed and executed [7,14,15]. These deimplementation strategies should be theory-and evidencebased and informed by analysis of barriers and facilitators that influence the use of low-value care, since this is expected to increase the adherence, adoption, and effectiveness of these de-implementation strategies [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that attempts to describe ANC, together with its antecedents and consequences, as experienced by students during their clinical rotations. Prior to recent studies (Bottega & Palese, 2020 ), ANC was reported mainly through anecdotal evidence as an expression of routines, traditions and rituals of nursing practice, and a potential issue of the theory–practice gap (Bourgault & Upvall, 2019 ; Rytterstrom et al., 2011 ; Shoghi et al., 2019 ), mostly from the perspective of nurses. However, the clinical environment permeates nursing education, enabling students to develop skills (Papastavrou et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…En lege beskrev det slik: «Når det gjelder å ta retningslinjer i bruk, tenker jeg at det er viktig med informasjon, at man skjønner hvorfor, at de Manglende faglige begrunnelse, eller det informantene oppfattet som ulogiske begrunnelser, hindret etterlevelse. Resultatet samsvarer med en kvalitativ studie blant sykepleiere på akuttmottak i USA, som beskriver hvordan kliniske anbefalinger uten tilstrekkelig faglig begrunnelse skaper usikkerhet (15).…”
Section: Forståelse Av Retningslinjerunclassified
“…Ifølge Fixsen og medarbeideres modell påvirker organisasjonsstruktur og kultur alle delene i implementeringsprosessen (9). Implementeringsstrategier bør fokusere mer på hvilke konsekvenser nye retningslinjer kan få for avdelingens eksisterende praksis (15). Klinisk helsepersonell kan bevisstgjøres på organisasjonens fagtradisjoner og verdier, og på hvordan disse kan påvirke etterlevelsen.…”
Section: Tilbakemeldinger -Kliniske Erfaringerunclassified